Influence of bio-based solvents on the catalytic reductive fractionation of birch wood. Issue 11 (10th September 2015) - Schutyser, W.; Van den Bosch, S.; Renders, T.; De Boe, T.; Koelewijn, S.-F.; Dewaele, A.; Ennaert, T.; Verkinderen, O.; Goderis, B.; Courtin, C. M.; Sels, B. F.
Abstract : In the reductive catalytic fractionation of lignocellulose, the choice of solvent significantly impacts the delignification efficiency, carbohydrate retention in the pulp and the macrostructure of the pulp. Abstract : Reductive catalytic fractionation constitutes a promising approach to separate lignocellulose into a solid carbohydrate pulp and a stable liquid lignin oil. The process is able to extract and convert most of the lignin into soluble mono-, di- and oligomers, while retaining most of the carbohydrates in the pulp. This contribution studies the impact of the solvent choice on both pulp retention and delignification efficiency. Several bio-derivable solvents with varying properties were therefore tested in the Pd/C-catalyzed reductive liquid processing of birch wood. Though a high solvent polarity favors delignification, a too polar solvent like water causes significant solubilization of carbohydrates. A new empirical descriptor, denoted as 'lignin-first delignification efficiency' (LFDE), is introduced as a measure of efficient wood processing into soluble lignin derivatives and solid sugar pulp. Of all tested solvents, methanol and ethylene glycol showed the highest LFDE values, and these values could be increased by increasing both reaction time and temperature. Moreover, substantial differences regarding the process characteristics and analyzed product fractions between these two different solvents were discussed extensively. Most striking is the impact of the solvent on the pulp macrostructure, with methanol yielding a pulp composed of aggregated fiber cells, whereas the ethylene glycol pulp comprises nicely separated fiber cells.